The Dutch sappanwood trade in the eighteenth century - Cameron J. G. Dodge (Essays in Economic & Business History (EEBH), 2021)
In the eighteenth century, the Dutch East India Company (VOC) traded sappanwood, a source of red dye for textiles, in both its Dutch-Asiatic and intra-Asian trade routes. The voyage and cargo records kept by the VOC's bookkeeper-general in Batavia reveal a small but convenient trade that complemented the Company's better-known dealings in spices and textiles. The VOC shipped Siamese and Indonesian sappanwood to the Dutch Republic and Asian markets regularly but in small quantities relative to other goods. Sappanwood was a useful ballast for VOC ships resulting in low-cost shipping for the commodity. In Europe, the VOC earned healthy margins by upplying a competitive red dyestuff to the continent's burgeoning textile industry. In Asia, sappanwood contributed to the VOC's intra-Asian trade system as a commodity useful in acquiring more lucrative goods, especially copper from Japan.
Keywords: 330; Sappanwood; Dutch East India Company (VOC); Bookkeeper-General Batavia; Dutch-Asiatic Trade; Intra-Asian Trade